Reverse direction transmission using single data frame and multi data frames to improve the performance of mac layer based on IEEE 802.11N - Ahmad Milad, Ali; Muhamad Noh, Zul Azri; Shibghatullah, Abdul Samad; Mustapha, Aouache; Algaet, Mustafa Almahdi (Publications International, 2014)
Reverse direction transmission and block ACK are effective ways to improve the performance of MAC layer that reduces the overhead and increases the system throughput. As high as 600 Mbps of physical data rate is achieved in IEEE 802.11n where high data rate of the current MAC layer leads to a high performance overhead and low performance throughput. Further,designing the MAC layer is still ongoing to achieve high performance throughput. In this paper, we examine the performance enhancement of the proposed 802.11n MAC layer in terms of reverse direction transmission using a single data frame and multi data frames. We implemented these schemes in the NS2 simulator to show the results for TCP traffic and compared them with the literature.